Collaborative policy innovation despite competition: A study of diffusion of health innovations across Dutch hospitals. - Frankowski, Andrea (Innovation Journal, 2023)
This study examines how policy innovations are disseminated through collaboration in a public context shaped by competition. It builds on the literature of collaborative policy innovation and describes public innovation both as a policy approach – the joint development of new and enriched policy solutions by networks of actors – and as an intended outcome. The study focuses on healthcare innovations in relation to the underexposed topic of diffusion: the final phase of the innovation process in which innovations are shared and spread. While earlier stages of the policy innovation process, e.g. invention and implementation, receive more attention, diffusion seems particularly hard to achieve in a competitive public context, since it requires a transformation of competing interests into collective action in a stage where it seems more beneficial to withhold competitors from access to innovations. However, an indepth case study in Dutch hospital care reveals that organizational benefits, reputational gains and legitimacy pressures enable diffusion – both in exclusive networks of hospitals (regimes) and sector-wide (beyond regimes). This paper shows how competition strengthens, rather than weakens, collaboration for policy innovation and has implications for both research and practice, in particular in relation to scaling, transfer or translation of public sector innovations. The study contributes to a better understanding of conditions under which collaborative policy innovation thrives in public sectors that are (partially) composed of competitive market mechanisms, by specifying policy innovation requirements that align the two seemingly contradictory perspectives of collaboration and competition.